PENGARUH KONFLIK TERHADAP WATAK TOKOH DALAM NOVEL BUMI AYU KARYA RESTIANA PURWANINGRUM - Puspa Anggreni; Martono Martono; Agus Wartiningsih (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis research focused to analysist conflict internal and external affect to the character ini novel Bumi Ayu by Restiana Purwaningrum. Researcher focused on conflict because the direct or indirect conflict in this novel has an impact or influence on character traits. Researcher used descriptive research method, and qualitative research form, with study of behavioristic literary psychology. Data source in this research is Bumi Ayu novel by Restiana Purwaningrum. The data of this research is quotes in the novel in the form of words, phrases, and sentences. Technique used in this research is study documentary technique. Data colleting tool is the researcher as the key instrument and assisted with note tools. Reseacher was able to analyze 7 individuals who experienced internal conflict, (1) Dara Kirai, (2) Apai Dolan, (3) Inai Ranggai, (4) Byan Borneo, (5) Samuel, (6) Bumi Ayu, (7) Rimba Samudera. External conflict includes physical conflict and social conflict. The  physical conflict is (1) Dara Kirai and (2) Bumi Ayu. A social conflict (1) Inai Ranggai and Mr. Salomo;   (2) Mr. Oti and Mr. Ori; (3) Byan Borneo and Dara Kirai; (4) Obet and Uncle Liyan; (5) Byan Borneo and Obet.Keywords: Character, Internal and External Conflict, Novel